Efektivitas Model UNIEC dalam Meningkatkan Kreatifitas Gerak Tari pada Siswa Sekolah Dasar - Syakhruni; Jalil; Prusdianto (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Creative power (creativity) is one of the potentials that children have that is important to develop from an early age. Every child has creative talents and in terms of education, creative talents can be developed. The UNIEC model makes dance learning in elementary schools have other advantages than just being able to demonstrate students' dancing skills on a stage that can be watched by many people, so that the UNIEC model can be used in elementary schools to enhance the development of creativity. This study uses action research. The school used as the research location was Class III of SD Negeri 4 Rappang. The data collection instrument used was the student activity observation sheet. The next instrument used is the student's ability observation sheet.